Pengaruh Brand Image dan Kredibilitas Pemain Tim Nasional terhadap Loyalitas Konsumen di Media Sosial - Fazilla, Meutia (Communicology: Jurnal Ilmu Komunikasi, 2025)
Intense competition in Indonesia’s bottled drinking water industry encourages brands to optimize digital marketing strategies to strengthen consumer loyalty. Le Minerale has demonstrated market share growth amid Aqua’s dominance, partly through Instagram-based marketing involving Indonesian National Football Team players as endorsers. However, previous studies tend to examine brand image and endorser credibility separately, leaving a gap in understanding their combined influence on consumer loyalty in social media contexts. This study aims to analyze the effects of Le Minerale’s brand image and the credibility of national team players on consumer loyalty on Instagram (@le_mineraleid) using the Integrated Marketing Communication (IMC) framework. A quantitative survey method was employed, collecting primary data from 400 followers of @le_mineraleid who had been exposed to promotional content featuring national team players, selected through purposive sampling. Data were analyzed using multiple linear regression, t-tests, and F-tests after validity, reliability, and classical assumption tests. The results indicate that both brand image and endorser credibility have a positive and significant effect on consumer loyalty, both partially and simultaneously, with a contribution of 64.3%. These findings highlight the effectiveness of integrating brand image and credible endorsers in digital marketing strategies to enhance consumer loyalty on social media platforms.